(untitled) (International Journal of Environmental Sciences, 2025)
Cynical rhetoric has become a prominent feature of contemporary political discourse, reflecting the growing mistrust between political leaders and their constituents. This study investigates the use of cynical pragma-rhetorical strategies in U.S. and Middle Eastern presidential political speeches, with a focus on how politicians construct distrust, sarcasm, and mockery to discredit opponents, challenge institutional credibility, or appeal to voter disillusionment. By examining selected presidential political speeches from both contexts, this research aims to identify and compare the linguistic markers, pragmatic functions, and persuasive effects of cynical language across cultural and political settings. The study is grounded in pragma-rhetorical theory, drawing on insights from speech act theory of Searle, J. R. (1969), politeness theory of Brown, P., & Levinson, S. C. (1987), and pragma-rhetorical criticism of Adam, J.-M., & Bonhomme, M. (2005). Cynical expressions are analyzed as contextualized speech acts that perform both ideological and interpersonal functions (Fairclough: 2000). The research also considers cultural factors, such as differing political traditions, freedom of expression, and audience expectations, which influence the form and function of cynical rhetoric. Examples are drawn from political speeches involving U.S. figures such as Donald Trump, and Middle Eastern candidates from countries such as Iraqi Prime Minister Mohammed Shia’ Al-Sudani, where political speeches are increasingly exposed but shaped by distinct sociopolitical realities. Comparative analysis reveals that while U.S. candidates tend to use direct irony, personal attacks, and populist mockery to frame themselves as anti-establishment or authentic, Middle Eastern candidates often employ indirect cynicism, religious or cultural allusions, and coded criticism to navigate political taboos and maintain social face. These differences highlight how cynicism is culturally adapted yet globally relevant as a political tool. Despite these variations, the rhetorical goal remains consistent: to expose contradictions, undermine rivals, and resonate with public frustration. This study contributes to the fields of pragma-rhetorics, political linguistics, and discourse analysis by offering a cross-cultural lens on a pragma-rhetorical strategy that is increasingly shaping democratic and authoritarian discourse alike. By examining the pragma-rhetorics of cynicism in both Western and non-Western contexts, it deepens our understanding of how political language reflects and constructs social realities, challenges institutional legitimacy, and influences populist attitudes in an era of global political unrest.